EPH22 Prevalence and risk factors of post COVID-19 condition in previously hospitalized patients in Bolivar, Colombia: an observational study (2022)
Objectives: To estimate the prevalence and risk factors of post-COVID-19 condition after at least three months of hospital discharge in a retrospective cohort of patients from a health insurance company (Mutual SER EPS) living in the north of Bolivar, a department of Colombia. Methods: Clinical and sociodemographic data were collected from 181 COVID-19 patients who were hospitalized in the ward or intensive care unit (ICU) between March-2021 to August-2021. Patients who agreed to participate were evaluated by a structured telephone interview to identify persistent or new symptoms after at least three months of hospital discharge. Associations between at least one symptom and clinical and sociodemographic characteristics at admission were assessed through bivariate and multivariate logistic regression using a stepwise Akaike information criterion (AIC) selection. Adjusted odds ratios (aOR) are reported. Results: Mean age of patients was 56 years (SD: 17 years), 50.8% (n=92) were women and 23.2% (n=42) were previously admitted to ICU. One-hundred-three patients (56.9%) had at least one comorbidity; being hypertension (36.5%), type 2 diabetes mellitus (18.2%) and heart disease (8.28%) the most common. The presence of at least one symptom after three months of hospital discharge was reported by 141 (77.9%) patients. Most frequently symptoms were fatigue (54.1%), joint pain (45.3%), dyspnea (43.1%), sleep disorders (36.5%), chest pain (30.4%), and anorexia (30.4%). Symptoms were significantly more frequent in women (aOR: 2.45, 95% CI 1.14- 5.29, p=0.02) and ICU admitted patients (aOR: 3.10, 95% CI 1.02-9.45 p=0.05), but were not associated with age, having comorbidities, or a previous long hospital stay. Conclusions: As reported in other studies, in Bolivar -Colombia, the presentation of post COVID-19 symptoms is frequent in previously hospitalized patients. Being a wome.